The #MeToo Movement and Ovid's Philomela - Barker, Justin L. (Radical Teacher, 2018)
This essay disucsses Ovid's Philomela in the context of the #MeToo Movement. It engages the problems of power and the use of masculine violence to silence female voices, and the ways these problems transcend time and culture. It then reflects on the potential for teaching Ovid alongside the #MeToo discourse.